Our land, our stories : upper primary : culture - Fuller, Lisa; Australian Institute of Aboriginal Studies (South Melbourne, Victoria : Cenage Learing Australia in partnership with AIATSIS, 2019)
Our Land, Our Stories is a landmark educational series exploring Aboriginal and Torres Strait Islander histories, peoples and cultures developed by Nelson, A Cengage Company in collaboration with the Australian Institute of Aboriginal and Torres Strait Islander Studies (AIATSIS). Developed over three years, with more than thirty five Aboriginal and Torres Strait Islander people contributing stories to the ground-breaking primary school resource, the series is a media-rich educational package developed for lower, middle and upper primary. All resources explicitly link to the Australian Curriculum Aboriginal and Torres Strait Islander cross-curriculum priority – Aboriginal and Torres Strait Islander histories and cultures – through exploring the three key concepts of Country/Place, Culture and People. The series was written by, and in consultation with, First Australians. The Upper Primary Culture Big Book in the Our Land, Our Stories series explores the widely diverse cultures of Aboriginal and Torres Strait Islander peoples. It invites the reader to recognise and celebrate the differences between all cultures. This book also discusses stereotypes and biases, how they play out in our culture today and what we can do to try to avoid thm.
Title from cover.
"Aboriginal and Torres Strait Islander peoples are advised that this text may contain the names and images of people who have passed away"--Table of contents page.
Keywords: Aboriginal Australians; Aboriginal Australians -- Study and teaching (Secondary); Education -- Teaching -- Materials; Education - Secondary - Curriculum; Culture; Race relations - Racism - Stereotyping; Australian